The effectiveness of massage for reducing pregnant women's anxiety and depression; systematic review and meta-analysis. (November 2020) - Hall, HG.; Cant, R; Munk, N.; Carr, B.; Tremayne, A.; Weller, C; Fogarty, S; Lauche, R.
Highlights: Anxiety and depression are common during pregnancy. Massage therapy may be effective in reducing pregnant women's anxiety and depression. High-quality research is required to properly evaluate the impact of massage therapy on pregnancy related anxiety and depression. Abstract: Objective: To critically appraise and synthesize the best available evidence on the effectiveness of massage to reduce antenatal women's anxiety and/ or depression. Design: Systematic review with meta-analysis Participants, interventions: Pregnant women over the age of 18 years who receive massage interventions. Measurements and findings: Eight studies were included in the review; seven were randomized controlled trials. Data were collected via pregnant women's self-reported ratings of anxiety or depression using validated tools. Meta-analysis of four studies revealed a moderate effect of massage therapy on women's depressive symptoms as measured by the Center for Epidemiologic Studies Depression Scale (CES-D) (MD = -5.95, 95%CI = -8.11 to -3.80, I 2  = 0%) compared with usual care. A moderate effect of massage interventions on women's anxiety were also found based on five studies using various measures (SMD = -0.59, 95%CI = -1.06 to -0.12, I 2  = 75%) when compared with usual care. However, none of the trials had a low risk of bias. Key conclusions: Non-pharmacologic treatments for mental health symptoms are an important option for women to use during pregnancy. As shown in meta-analysed data, massage therapy might be more effective in reducing pregnant women's anxiety and depression than usual care, although the current results may be prone to bias. Further high-quality research is required to fully evaluate the impact of massage therapy on pregnant women's mental health symptoms in the immediate and also longer term. Implications for practice: Massage therapy may be an acceptable and feasible approach for pregnant women to employ to reduce their anxiety and depressive symptoms. More research evidence examining the safety and effectiveness of massage is required before practice recommendations can be made.